Pengembangan Lokasi Agroindustri Buah-Buahan Di Kabupaten Indramayu Jawa Barat - Juri Juswadi; Pandu Sumarna (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
The aim this research is to plan the location development of fruit agroindustry in Indramayu Regency. The Identification of the fruit agroindustry location is based on the cost efficiency of fruit supplies transportation as raw materials, which are produced by 31 sub-districts. In this development plan, Indramayu district is divided into four regions based on the closesness of the location and the production of mango, banana, papaya, guava, watermelon, and sapodilla. The determination of the agro-industry location is based on the center of gravity method. Research data on fruit production is taken from the Central Bureau of Statistics of Indramayu Regency. The location data of each district was obtained from google maps. The results of data analysis show that the mango agroindustry location development is located at Terusan-Sindang village in Region I, Arjasari-Patrol village in Region II, Tanjung Kerta-Kroya village in Region III and Tambi Lor-Sliyeg village in Region IV. The development of banana argoindustry location is located in Bojangsari-Indramayu village in Region I, Bongas-Bongas village in Region II, Gantar-Gantar village in Region III and Cangkingan-Kedokanbunder village in Region IV. The Development of Papaya agroindustry location is found in Karanganyar-Indramayu village in Region I, Kertamulya-Bongas village in Region II, Kroya-Kroya village in Region III and Pilangsari-Jatibarang village in Region IV. The guava agroindustry location development is found in Karangmalang- Indramayu village in Region I, Cipaat-Bongas village in Region II, Mekarjati-Haurgeulis village in Region III and Bulak-Jatibarang village in Region IV. The development of watermelon agrioindustry location is situated in Karanganyar-Indramayu village in Region I, Jatimunggul-Terisi village in Region III and Jayalaksana- Kedokanbunder village in Region IV. The development of sapodilla agroindustry location is in Karangmalang- Indramayu village in Region I, Lempuyang-Anjatan village in Region II, Sumbon-Kroya village in Region III and Tambi Lor-Sliyeg village in Region IV.